2012
DOI: 10.1111/j.1532-849x.2012.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Straight and Offset Implant Placement under Axial and Nonaxial Loads in Implant‐Supported Prostheses: Strain Gauge Analysis

Abstract: There was evidence that offset placement is capable of reducing the strain around an implant. In addition, the type of loading, axial force or nonaxial, did not have an influence until 2 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…Concerning to the linear positioning of the strain gauges, this study is in agreement of the study conducted by Heckmann et al, 2004, among others, who studied the microstrain around the implants with 3-element superstructures [30,[32][33][34][35][36][37][38]. This position justifies the little variation found in the microstrain means of the non-axial loads executed by this present study, and the highest values were found in the points farthest from the implant e (A' and B').…”
Section: Discussionsupporting
confidence: 84%
“…Concerning to the linear positioning of the strain gauges, this study is in agreement of the study conducted by Heckmann et al, 2004, among others, who studied the microstrain around the implants with 3-element superstructures [30,[32][33][34][35][36][37][38]. This position justifies the little variation found in the microstrain means of the non-axial loads executed by this present study, and the highest values were found in the points farthest from the implant e (A' and B').…”
Section: Discussionsupporting
confidence: 84%
“…All the studies found were in vitro and computer simulations, and among them, five used 3D finite element analysis (FEA), five strain gauge analysis, one 3D geometric analysis, and one photoelastic stress analysis . No clinical study was found (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Biomechanically, the concept of the buccal or lingual offset configuration implants was proposed to safely and effectively decrease the risk of occlusal overload in implant‐retained fixed partial prostheses in the posterior region and to reduce bending in the implants . This concept has been associated with improving the restoration's biomechanical stability, which could reduce the loosening or fracturing of screws and implants .…”
mentioning
confidence: 99%
“…Reported studies verifying the effects of offset placement include ones where implant bodies were embedded in rectangular experimental models [1114], ones where rectangular bone models were constructed with FEA models [15, 16], and ones where FEA models were constructed from CT data on human mandibles [17, 18]. The artificial mandible models used in the present study were type II in the Lekholm and Zarb classification [24] and created using clinically valid estimates of bone quality, bone structure, and bone morphology.…”
Section: Discussionmentioning
confidence: 99%